Sleep disordered breathing and daytime hypoventilation in a male with MECP2 mutation. Issue 12 (21st September 2020) - Cacciatori, Elena; Lelii, Mara; Russo, Silvia; Alari, Valentina; Masciadri, Maura; Guez, Sophie; Patria, Maria Francesca; Marchisio, Paola; Milani, Donatella
Abstract: Rett syndrome (RTT, MIM * 312750) is an X‐linked neurodevelopmental disorder caused by pathogenic variants at the Xq28 region involving the gene methyl‐CpG‐binding protein 2 ( MECP2, MIM * 300005). The spectrum of MECP2 ‐related phenotypes is wide and it ranges from asymptomatic female carriers to severe neonatal‐onset encephalopathy in males. Abnormal breathing represents one of the leading features, but today little is known about polysomnographic features in RTT females; no data are available about males. We report the case of a male of Moroccan origins with a MECP2 pathogenic variant and a history of encephalopathy and severe breathing disturbances in the absence of dysmorphic features. For the first time we describe in detail the polysomnographic characteristics of a MECP2 ‐mutated male and we show the relevance of severe central apneas, which may represent a new clinical clue to suggest the diagnosis. Moreover, we want to highlight the importance to maintain a high index of suspicion for MECP2 ‐related disorders in the presence of severe hypotonia, apneic crises, and respiratory insufficiency in males to permit an earlier diagnosis and the consequent definition of recurrence risk of the family and to avoid other useless and invasive exams.